Oviposition by a Specialist Herbivore Increases Susceptibility of Canola to Herbivory by a Generalist Herbivore. Issue 3 (29th April 2022) - Weeraddana, Chaminda De Silva; Evenden, Maya L
Abstract: Oviposition by specialist herbivores can alter the suitability of the host plant to subsequent infestation by other herbivores. In this study, we tested the effect of previous oviposition on canola, Brassica napus L., by a Brassica specialist, the diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), on subsequent herbivory by the generalist feeder, the bertha armyworm (BAW), Mamestra configurata Walker (Lepidoptera: Noctuidae). The effect of DBM oviposition on subsequent BAW oviposition and larval feeding was tested in no-choice and choice experiments. Oviposition of BAW was not altered by DBM eggs on canola plants, however, BAW had increased larval feeding on plants with DBM eggs. These results suggest that oviposition by a specialist herbivore increased the susceptibility of the host plant to generalist herbivory. In a preliminary experiment, salicylic acid, jasmonic acid, and its conjugates were not altered by DBM oviposition on canola, however, further experimentation is needed to determine if oviposition affects expression of plant defense pathways and other plant traits.